To the King's Most Excellent Majesty in council memorial of Benjamin Lacam from New Harbour in Bengal - Lacam, Benjamin (s.n, 1782)
Appealing against the East Company's cancellation of their grant to him of the New Harbour, which he was to develop into a dockyard for warships